Nitric oxide and salt resistance in Dahl rats: no role of inducible NO synthase - Zicha, J; Řezáčová, L; Vaněčková, I (Physiological research, 2023)
Inducible NO synthase (NOS II) was proposed to play an important role in salt resistance of Dahl salt-resistant (SR/Jr) rats. Its chronic inhibition by specific inhibitors was accompanied by blood pressure (BP) elevation in animals subjected to high salt intake. The aim of our study was to evaluate 1) whether such inhibitors affect BP and/or its particular components (sympathetic tone and NO-dependent vasodilation) only under the conditions of high salt intake, and 2) whether similar BP effects are elicited after systemic or intracerebroventricular (icv) application of these inhibitors. Wistar rats fed Altromin diet (0.45 % NaCl) and SR/Jr rats fed either a low-salt (LS, 0.3 % NaCl) or a high-salt (HS, 4 % NaCl) diet were studied. Aminoguanidine (AMG) and 2-amino-5,6-dihydro-6-methyl-4H-1,3-thiazine (AMT) were used as NOS II inhibitors. BP and its responses to acute blockade of renin-angiotensin system (captopril), sympathetic nervous system (pentolinium) and NO synthase (L-NAME) were measured in conscious cannulated rats. There were no significant changes of BP or its components in either Wistar rats or SR/Jr rats subjected to chronic inhibition of NOS II by peroral aminoguanidine administration (50 mg/kg/day for 4 weeks). This was true for SR/Jr rats fed either LS or HS diets. Furthermore, we have studied BP effects of chronic icv administration of both NOS II inhibitors in SR/Jr rats fed HS diet, but we failed to find any BP changes elicited by such treatment. In conclusion, inducible NO synthase does not participate in the resistance of SR/Jr rats to hypertensive effects of excess salt intake.
Keywords: Nitric Oxide; hypertenze; Rats, Wistar; potkani inbrední Dahl; Sodium Chloride; Nitric Oxide Synthase Type II; oxid dusnatý; potkani Wistar; Hypertension; Rats, Inbred Dahl; chlorid sodný; Sodium Chloride, Dietary; krysa rodu Rattus; Animals; krevní tlak; zvířata; Nitric Oxide Synthase; synthasa oxidu dusnatého; Rats; Blood Pressure; synthasa oxidu dusnatého, typ II; kuchyňská sůl